Educational leadership for social justice and improving high-needs schools : findings from 10 years of international collaboration - Barnett, Bruce G.; Woods, Philip A., 1950- (International research on school leadership., 2021)
"To commemorate the 10-year anniversary of the International School Leadership Development Network (ISLDN), this book is a compilation of the work conducted by network scholars. This volume is the first comprehensive overview of the studies conducted by ISLDN members engaged in examining how social justice leaders and leaders of high-need schools address the social conditions, learning experiences, and performance of their students. Other international school leadership research consortia have emerged in the 21st century; however, the ISLDN is the second longest operating project, after the International Successful School Principalship Project (ISSPP). Since its creation in 2010, ISLDN scholars have delivered papers at a variety of international conferences and shared findings in research publications, including books and special issues of journals. Until now, ISLDN research findings have been disseminated separately for the project's two strands: (a) social justice leadership and (b) leadership in underperforming high-need schools. Therefore, the purpose of the book is to document the history and evolution of the ISLDN and to provide descriptions and reflections of the project's research findings, methodologies, and collaborative processes across the two strands. This volume captures studies of school leaders from 19 countries representing six continents - Africa, Asia, Australia and Oceania, Europe, North America, and South America. The authors examine important external and internal contextual factors influencing schools in different cultural settings and provide insights about the values and practices of social justice leaders working in high-need school settings. Numerous practical strategies are provided for school leaders working in schools with similar conditions. The concluding chapter by the co-editors synthesizes the structural factors, personal beliefs and values, and contextualized change management strategies that shape school leaders' actions aimed at ensuring the best learning outcomes for their students. Besides capturing the range of findings emerging from various ISLDN studies conducted over the past decade, several chapters critically examine the project's current contributions to the field. Authors suggest broadening the dissemination of our findings to increase the visibility of the project, expanding the research methods beyond qualitative interviews, incorporating studies from non-Anglophone countries, and augmenting the scope of our analyses and research focus. These researchers' journeys also reveal the obstacles to and benefits of engaging in these types of international collaborative research ventures"--